2003
DOI: 10.1038/sj.onc.1206915
|View full text |Cite
|
Sign up to set email alerts
|

v-Src inhibits myogenic differentiation by interfering with the regulatory network of muscle-specific transcriptional activators at multiple levels

Abstract: The conversion of skeletal myoblasts to terminally differentiated myocytes is negatively controlled by several growth factors and oncoproteins. In this study, we have investigated the molecular mechanisms by which v-Src, a prototypic tyrosine kinase, perturbs myogenesis in primary avian myoblasts and in established murine C2C12 satellite cells. We determined the expression levels of the cell cycle regulators pRb, cyclin D1 and D3 and cyclindependent kinase inhibitors p21 and p27 in v-Srctransformed myoblasts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 63 publications
1
21
0
1
Order By: Relevance
“…Consistently, accumulation of musclespecific proteins was also increased (Figure 2d), clearly Signalling pathways in v-Src myoblasts L Ciuffini et al indicating that inhibition of MEK activity promoted differentiation of v-Src-transformed myoblasts. We had previously shown that forced expression of the cdk inhibitor p27 causes QMb-LA29 to exit from the cell cycle, yet does not promote myogenic differentiation (Falcone et al, 2003). To determine whether the MEK pathway is directly involved in the v-Src block of differentiation or acts by keeping cells proliferating (Figure 1b), we infected QMb-LA29 with adenoviruses encoding for p27 and b-gal and, after 24 h, added PD98059 or U0126 to the culture medium for 2 days.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistently, accumulation of musclespecific proteins was also increased (Figure 2d), clearly Signalling pathways in v-Src myoblasts L Ciuffini et al indicating that inhibition of MEK activity promoted differentiation of v-Src-transformed myoblasts. We had previously shown that forced expression of the cdk inhibitor p27 causes QMb-LA29 to exit from the cell cycle, yet does not promote myogenic differentiation (Falcone et al, 2003). To determine whether the MEK pathway is directly involved in the v-Src block of differentiation or acts by keeping cells proliferating (Figure 1b), we infected QMb-LA29 with adenoviruses encoding for p27 and b-gal and, after 24 h, added PD98059 or U0126 to the culture medium for 2 days.…”
Section: Resultsmentioning
confidence: 99%
“…Although exit from the cell cycle and commitment to differentiation are necessarily linked processes, inhibition of myogenesis by v-Src in both avian and murine myoblasts can occur independently of cell proliferation (Falcone et al, 2003). In myocytes, v-Src negatively affects transcription of muscle-specific genes by targeting the function of MRFs, in part by interfering with their interaction with co-regulators that control chromatin remodelling (Falcone et al, 2003). However, the cytoplasmic pathways activated by v-Src that convey the inhibitory signals from the cell periphery to the nucleus, eventually leading to block of musclespecific transcription, have not yet been defined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2o) p27 kip -há uma relação inversa entre a capacidade proliferativa da CS e a abundância da proteína p27 Kip, podendo estar envolvida no crescimento e na hipertrofia musculares (27) . 2p) v-Src -é uma típica tirosina-quinase, inibindo a diferenciação miogênica por meio da inibição da expressão de MyoD e miogenina (28) . Outros candidatos a marcadores das CS encontram-se em investigação: o antígeno de superfície celular Sca-1 (29)(30) , a glicoproteína Leu-19, o fator anti-apoptótico Bcl-2 (31)(32) , entre outros.…”
Section: Marcadoresunclassified